KAJIAN LINGUISTIK FORENSIK KASUS VICKY PRASETYO DAN ANGEL LELGA DALAM KASUS PENCEMARAN NAMA BAIK - Ubaidah, Rafika; Ayu Setianingrum, Firda; Dwi Novari, Rintan; Casim (UNIVERSITAS PGRI YOGYAKARTA, 2024)
This research was motivated by the defamation carried out by Vicky Prasetyo against Angel Lelga who was suspected of having an affair with Fiki Alman. This research aims to analyze language crimes from a semantic perspective in the case of defamation of Angel Lelga committed by Vicky Prasetyo. This research uses a qualitative type. descriptive method. Data collection techniques in the form of observation and documentation.